Encylopedia of Indian philosophies; Vol IV Samkhya A dualist tradition in Indian philosophy - Bhattacharya, Ram Shankar; Larson, Gerald James (ed) (Delhi Motilal Banarsidas, 2006)
Introduction to the philosophy of Samkhya